Prospective Validation Study of a Predictive Score for Operability of Recurrent Ovarian Cancer: The Multicenter Intergroup Study DESKTOP II. A Project of the AGO Kommission OVAR, AGO Study Group, NOGGO, AGO-Austria, and MITO. Issue 2 (1st January 2011) - Harter, Philipp; Sehouli, Jalid; Reuss, Alexander; Hasenburg, Annette; Scambia, Giovanni; Cibula, David; Mahner, Sven; Vergote, Ignace; Reinthaller, Alexander; Burges, Alexander; Hanker, Lars; Pölcher, Martin; et al.
Abstract : Purpose: The DESKTOP I trial proposed a score for the prediction of complete cytoreduction in recurrent ovarian cancer. Resectability was assumed if 3 factors were present: (1) complete resection at first surgery, (2) good performance status, and (3) absence of ascites. The DESKTOP II trial was planned to verify this hypothesis prospectively in a multicenter setting. Methods: Participating centers prospectively enrolled all consecutive patients with platinum-sensitive first or second relapse. The score was applied to all patients, but centers were free to decide on therapy. All further therapies were documented, and the outcome of patients was analyzed. A 75% complete resection rate in 110 prospectively classified patients had to be achieved to confirm a positive predictive value of 2 or higher of 3 with 95% probability. Results: A total of 516 patients were screened within 19 months; of these, 261 patients (51%) were classified as score positive, and 129 patients with a positive score and first relapse were operated on. The rate of complete resection was 76%, thus confirming the validity of this score regarding positive prediction of complete resectability in 2 or more of 3 patients. Complication rates were moderate including second operations in 11% and perioperative mortality in 0.8%. Conclusions: This score is the first prospectively validated instrument to positively predict surgical outcome in recurrent ovarian cancer. It can aid in the selection of patients who might benefit from secondary cytoreductive surgery and will be enrolled in the recently started randomized prospective DESKTOP III trial investigating the role of surgery in recurrent platinum-sensitive ovarian cancer.